2011
DOI: 10.19030/iber.v5i10.3515
|View full text |Cite
|
Sign up to set email alerts
|

Market Concentration And Industry Profitability: The Case Of Greek Banking (1997-2004)

Abstract: An empirical investigation of the relationship between market concentration and performance in the Greek banking, this paper finds that market concentration has a weak effect on bank profitability. This finding could be attributed to the long tradition of the Greek governments to keep the financial institutions under immediate either in the form of state-owned institutions or indirectly through a complex and rigid regulations concerning interest rates, credit standards and credit rationing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…The lack of competitive pressures in the Greek banking sector could explain the deviation of the country's transition coefficients from the panel average at the start of the period. However, the Greek banking sector has undergone several changes, most notably moving away from close ownership and management by the government in the late 1990s together with the implementation of several EU directives (Maniatis, 2006). The wave of consolidation and introduction of competition may well explain the subsequent movement of the country's time path towards the panel average.…”
Section: Deposit Rates (>2years' Maturity): 2003-2008mentioning
confidence: 99%
“…The lack of competitive pressures in the Greek banking sector could explain the deviation of the country's transition coefficients from the panel average at the start of the period. However, the Greek banking sector has undergone several changes, most notably moving away from close ownership and management by the government in the late 1990s together with the implementation of several EU directives (Maniatis, 2006). The wave of consolidation and introduction of competition may well explain the subsequent movement of the country's time path towards the panel average.…”
Section: Deposit Rates (>2years' Maturity): 2003-2008mentioning
confidence: 99%
“…Les résultats obtenus corroborent les recherches anté-rieures (Schwalbach, 1991;Goldberg et Rai, 1996;Maniatis, 2006;Maudos et Guevara, 2008;Williams et al, 2009;Seelanatha, 2010). Ces recherches montrent l'existence d'une relation positive entre la part de marché et la profitabilité de la banque.…”
Section: Résultats Et Discussionunclassified
“…En fait, plusieurs recherches ont montré que le pouvoir de marché relatif (RMP) mène à des profits économiques importants et réduit le risque de la firme (Scott, 1986;Goddard et Wilson, 1999;Berger et al, 2000;Maniatis, 2006;Williams et al, 2009;Seelanatha, 2010). En effet, les grandes firmes détenant des parts de marché importantes ont l'avantage d'offrir sur le marché des produits différenciés (recherche et développement, publicité, localisation et emplacement, autres avantages).…”
Section: H1 La Concentration De Marché a Un Effet Positif Sur La Perunclassified
“…While the majority of literature that adopted SCP model is found in the developed economies and mostly in the banking sector of such countries (Ferreira, 2014;Behname, 2012;Sahoo and Mishra, 2012;Park, 2012;Lee, 2012;Mensi and Zouari, 2011;Maniatis, 2006), few studies were conducted on pharmaceutical firms operating in developing economies (Vyas, et al 2012;Mishra and Chandra, 2010;Mishra and Vikas, 2010;Zhang & Li, 2009). Ogaji et al (2014) showed that the capacity utilization of the Nigerian pharmaceutical industry increased steadily but marginally over the period of 1984 to 2014.Furthermore, Ugbam and Okoro (2017) asserted that larger firms are more efficient in the pharmaceutical industry in Nigeria.…”
Section: Empirical Literaturementioning
confidence: 99%